A systematic review evaluating loneliness assessment instruments in older adults - Bugallo-Carrera, César; Dosil-Díaz, Carlos; Anido-Rifón, Luis; Pacheco-Lorenzo, Moisés; Fernández-Iglesias, Manuel J.; Gandoy-Crego, Manuel (Frontiers in Psychology, 2023)
Introduction and objectives The experiences and changes that come along with old age may lead to a feeling of loneliness, usually followed by negative physical and mental manifestations. In this systematic review, we evaluated the existing tools to assess loneliness in older adults. Methods We performed a literature search in the Web of Science, Medline, and PsycINFO, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After, we examined the psychometric properties of the instruments with a focus on reliability, validity, and main conclusions. Results We included 27 articles published between 1996 and 2021. Conclusion To date, there are few instruments to assess loneliness in older adults. In general, they present adequate psychometric properties, although it is true that some scales show somewhat low levels of reliability and validity.